Adicción a las redes sociales y autoestima en estudiantes del quinto ciclo de primaria de la institución educativa N° 61023 Rosa Licenia Vela Pinedo de Costa, Nauta 2024 - Ruiz Diaz, Juliana (2025)
The objective of this research was to establish the relationship between addiction to social networks and the level of self-esteem in students of the fifth cycle of primary education of Educational Institution No. 61023 “Rosa Licenia Vela Pinedo de Costa”, Nauta 2024. The methodology used was correlational, with a bivariate, field and transversal design, applying a sample of 123 students. A validated survey was used to measure the variables of addiction to social networks and self-esteem. The results show that there is a low, but significant positive assessment (rho = 0.325, p = 0.000), between both variables, which indicates that as addiction to social networks increases, the students' self-esteem also tends to increase. . , although the relationship is not strong. Furthermore, it will be observed that students with average self-esteem tend to present a moderate addiction to social networks, while those with high self-esteem may also present significant levels of addiction. These findings suggest the need to develop educational and family strategies that promote the responsible use of social networks and strengthen students' self-esteem, in order to mitigate the negative effects of addiction on their personal and academic development.